2003
DOI: 10.1124/jpet.102.046797
|View full text |Cite
|
Sign up to set email alerts
|

A Tertiary Alcohol Analog of γ-Hydroxybutyric Acid as a Specific γ-Hydroxybutyric Acid Receptor Ligand

Abstract: ␥-Hydroxybutyric acid (GHB) shows great promise as a treatment for sleeping disorders but is also increasingly abused. The exact mechanism of action of GHB is yet to be delineated, but it is known to interact with specific GHB binding sites or receptors, to act as a weak agonist at GABA B receptors, and that GHB undergoes metabolism to GABA. In drug discrimination studies, GABA B agonists, and to a lesser extent GABA A -positive modulators, substitute for GHB. To delineate the relative contributions of each re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
(50 reference statements)
1
15
0
Order By: Relevance
“…Several recent studies have employed drug discrimination procedures as an animal model of subjective drug effects to examine the pharmacological mechanisms underlying these effects (Winter 1981;Colombo et al 1995aColombo et al ,b, 1998Lobina et al 1999;Metcalf et al 2001;Carter et al 2003;Wu et al 2003;Baker et al 2004). Relatively few studies, however, have examined the discriminative stimulus effects of the GHB precursors, GBL and BDL.…”
Section: Introductionmentioning
confidence: 97%
“…Several recent studies have employed drug discrimination procedures as an animal model of subjective drug effects to examine the pharmacological mechanisms underlying these effects (Winter 1981;Colombo et al 1995aColombo et al ,b, 1998Lobina et al 1999;Metcalf et al 2001;Carter et al 2003;Wu et al 2003;Baker et al 2004). Relatively few studies, however, have examined the discriminative stimulus effects of the GHB precursors, GBL and BDL.…”
Section: Introductionmentioning
confidence: 97%
“…In a review of the neurobehavioral effects of GHB, Nicholson and Balster (2001) concluded that GHB does not appear to have discriminative stimulus properties that are consistently similar to any of the traditional classes of abused drugs. There is now a growing body of literature on the discriminative stimulus effects of GHB, and recent reports Wu et al 2003) suggest that these effects are mediated primarily by GABA B receptors.…”
Section: Introductionmentioning
confidence: 98%
“…As the dose of GHB is increased, additional mechanisms of action are likely to contribute to its behavioral profile. Thus, GHB or dopamine receptor-mediated mechanisms that do not seem to play a prominent role in the discriminative stimulus effects of GHB in rats (Winter, 1981;Wu et al, 2003;Carter et al, 2004a) could play a more predominant role in mediating the effects of GHB that are observed at larger doses.…”
Section: Novel Ghb Analogs: Binding and Behavioral Effects 1321mentioning
confidence: 99%
“…[ 3 H]GABA (10 nM) binding to GABA A receptors in cerebral cortex was performed in a similar manner, using a 10-min incubation period at 4°C, and GABA (100 M) to define nonspecific binding. Binding affinity for GABA B receptors was measured in tissue from cerebellum, an area where GHB binding to GABA B receptors has been shown previously (Mathivet et al, 1997;Wu et al, 2003). For [ 3 H]GABA (10 nM) binding to GABA B receptors in rat cerebellum, all of the assay tubes contained 40 M isoguvacine HCl (MP Biomedicals, Irvine, CA) to displace [ 3 H]GABA binding to GABA A receptors.…”
Section: Methodsmentioning
confidence: 99%